Pendidikan Karakter dalam Menanggulangi Kenakalan Remaja Berdasarkan Aspek â€œKnowledge, Feeling dan Actingâ€ - Aini, Alifiah Zahratul; Nurhani, Devi; Trifiriani, Muharrama (Ridwan Institute, 2021)
Indonesia is experiencing a youth crisis that has a strong character, this is evidenced by the development of the country and the high level of juvenile delinquency as a manifestation of the failure of teenagers in utilizing their potential. While on the other hand, teenagers as young people are expected to be in control of the country in the future, so that the youth (youth) can determine the direction of nation building. To make Indonesia grow more and more has a quality next generation. A quality generation can be formed through character education. The method in this study uses lietratur review method. Education must be more concerned and understand what to do to prevent juvenile delinquency, one way is to apply character education. Character education includes moral knowing, moral feeling, moral action, without cooperation between family and character education school in children will not be realized properly